THE IDEA OF GASSĀN HAMDŪN IN THE BOOK TAFSĪR MIN NASAMĀT AL-QUR'ĀN KALIMĀT WA BAYĀN - Abdullah, Hadrawi; Galib, Muhammad; Sabry, Muhammad Sadiq (Jurnal Diskursus Islam, 2022)
The purpose of this study is to find out the Idea of Gassan Hamdun in the book of Tafsir Min Nasamat al-Qur'an Kalimat wa Bayan which relates to interpretation techniques, writing systematics and their characteristics, advantages and disadvantages of the book. The results of this study show that Gassan Hamdun used the Ijmali method in interpreting verses from the Qur'an by being sourced from the tafsir bi al-ma'syour and other major tafsir books such as Tafsir Jalalain Tafsir Imam Nasafi, Tafsir Al-Alusi, Tafsir Ibn Kasir, Al-Jami' Li Ahkam al-Qur'an " by Imam Qurtubi tafsir "Fi Zilal al-Qur'an" by Sayyid Qutub. According to Gassan Hamdun the source of the interpretation of bi alma's}youris the most correct compared to other sources of variation, although he also made the book of interpretation bi al-ra'yi al mahmud, which is an interpretation that relies on ijtihad as the source of his understanding, such as the interpretation of al-Alusi. Gassan Hamdun presents a book of performances in which each arrangement uses a specific formula and code. This formula and code are the form initials of the letters, which aims to make it easier for the reader to know the reference to his interpretation and save the writing in his book to produce a beautiful book to read.